Usual source of care and the quality of primary care: a survey of patients in Guangdong province, China. Issue 1 (December 2015) - Du, Zhicheng; Liao, Yu; Chen, Chien-Chou; Hao, Yuantao; Hu, Ruwei
Abstract Introduction Usual source of care (USC) refers to the provider or place a patient consults when sick or in need of medical advice. No studies have been conducted in China to compare the quality of primary care provided with or without USC. The purpose of this study was to fill this gap in the literature by examining the quality of primary care provided between those having a USC and those without. Results of the study would provide implications for policymakers in terms of improving primary care performance in China, and help guide patients in their health care seeking behaviors. Methods A cross-sectional survey with patients was conducted in Guangdong province of China, using the Chinese validated Primary Care Assessment Tool (PCAT). ANOVA was performed to compare the overall and ten domains of primary care quality for patients with and without USC. Multivariate analyses were used to assess the association between USC and quality of primary care attributes while controlling for sociodemographic and health care characteristics. Results The study added evidence that having a USC can provide higher quality of primary care to patients than those without a USC. Results of this study showed that the PCAT score associated with those having a USC was significantly higher than those not having a USC. Moreover, the study showed that having a usual provider of care was also independently and significantly associated with patients' satisfaction with care. Conclusions This study added evidence that in China, patients with a USC reported higher quality of medical care experiences compared with those without a USC. The efforts to improve quality of care should include policies promoting USC.